(untitled) (المجلة الدولية للبحوث العلمية, 2024)
Background: congenital hand Syndactyly is prevalent with substantial aesthetic and functional implications, so the surgical separation of the fused fingers is essential in order to restore the hand function, enhance appearance and facilitate normal hand growth with less complications and procedures. Patients and Methods: the study is a descriptive prospective study is carried on 31 webs of 18 casas underwent surgical repair of congenital syndactyly during the period from august 2021 to august 2023 of different ages and sexes performed in Al- Gumhori Teaching Authority Hospital, Elite Hospital and police hospital. Results: the age of study population ranged between 2 - 25 years, and the majority of the patients belong to age the group above 13 years (66.7%), (N= 12) patients with median age of study 17.92 years; most of them are female with a common web involved between middle - ring fingers in (44.5%) (N=8) patients and frequently presented with simple complete syndactyly in (55.6%) (N=10), complex 22% and complicated 16.6%. The reconstructive technique for repair is dorsal rectangular flap with zig-zag interdigitating flaps. No intraoperative complications and there are postoperative complications like skin infections two webs, flap maceration one webs, partial graft loss two webs. Conclusion: the dorsal rectangular flap technique is preferred due to its simple design and easy modification during operation with smooth mobilization of the dorsal skin to achieve more natural web space with good results and can be applied in the majority of syndactyl types.